Convergence of Numerical Schemes for a Conservation Equation with Convection and Degenerate Diffusion - R. Eymard, R. Eymard; C. Guichard, C. Guichard; Xavier Lhébrard, Xavier Lhébrard (Journal of computational mathematics, 2021)
The approximation of problems with linear convection and degenerate nonlinear diffusion, which arise in the framework of the transport of energy in porous media with thermodynamic transitions, is done using a θ-scheme based on the centred gradient discretisation method. The convergence of the numerical scheme is proved, although the test functions which can be chosen are restricted by the weak regularity hypotheses on the convection field, owing to the application of a discrete Gronwall lemma and a general result for the time translate in the gradient discretisation setting. Some numerical examples, using both the Control Volume Finite Element method and the Vertex Approximate Gradient scheme, show the role of θ for stabilising the scheme.